Expression of the transcription factor Hes3 in the mouse and human ocular surface, and in pterygium - Economopoulou, Matina; Masjkur, Jimmy; Raiskup, Frederik; Ebermann, Doreen; Saha, Sarama; Karl, Mike O.; Funk, Richard; Jaszai, Jozsef; Chavakis, Triantafyllos; Ehrhart-Bornstein, Monika; Pillunat, Lutz E.; Kunz-Schughart, Leoni; et al. (Taylor & Francis, 2014)
Purpose: In this work we examined the presence of the neural stem cell biomarker Hairy and Enhancer of Split 3 (Hes3) in the anterior eye segment and in the aberrant growth condition of the conjunctiva pterygium. Further, we studied the response of Hes3 to irradiation.